Kita-Sozialarbeit als neues Berufsfeld zur Stärkung des Kinderschutzes Mit einem Vorwort von Prof. Dr. Tim Wersig und Prof. Dr. Regina Rätz - Wiethüchter, Christina (Young Academics: Frühe Hilfen und Kinderschutz, 2023)
As a reaction to the increased demands, daycare social work is establishing itself nationwide, expanding the range of services offered by daycare centers. Christina Wiethüchter explores the question to what extent this new professional field holds possibilities for strengthening child protection. Based on theoretical considerations about social work and child protection in daycare centers, interviews with daycare social workers are analyzed. Potentials on the levels of the children, the families, the daycare team, the daycare management and the network partners are identified. Particular potential is shown in the resource of daycare center social work to network all levels and to initiate, accompany and secure processes important for child protection.